Awareness of ikhtilat : a study among students of ACIS in UiTM Puncak Alam / Fara Camelia Adol Razzak - Adol Razzak, Fara Camelia (2019)
From the general view, we can see there are problems from the way people such as teenager and adults these days mix in between both genders. Most of them always sit together closely with almost no gap between them. They also do not manage the supposed manners between males and females. For example, they laugh loudly. This behaviour is not wrong. However, for females, it is only limited among the same gender and people who have a mahram relationship with them such as parents and siblings. The objectives of this research are to know the level of knowledge of the students about the limits of ikhtilat, to allow the students to know what careless ikhtilat can lead and to search whether the students know the ways to manage their ikhtilat with the opposite gender. This research uses a quantitative method as it is more appropriate to the subject intended to be studied. Quantitative approaches using questionnaires through online forms were applied in this study to ease respondents and to attract them to respond and to give feedback on this study. The data were analysed using Microsoft Excel to get the results of the questionnaire distributed through the online form. The result of the study suggested that students to strengthen their faith (iman) so that they can prevent themselves from doing bad things involving ikhtilat. The result of the study also suggested that parents must put their children into schools that have Islamic education as the compulsory subject in the syllabus so that the children can learn and increase their knowledge about ikhtilat. It is hoped that the study can contribute to the improvement of the students nowadays regarding the awareness of ikhtilat.